Effect of Anesthetics on Oxidant and Antioxidant Parameters After Inguinal Hernia Surgery in Older Patients - Raheleh Alimoradzadeh; Mohammad Amin Abbasi; Forough Zabihi; Hossein Mirmiranpour (University of Social Welfare & Rehabilitation Sciences, 2021)
Objectives: The effects of anesthesia techniques and anesthetics on different systems and organs of the body, especially the immune system, in older patients undergoing surgery, have always been of interest to researchers. This study aims to compare the effects of general anesthesia with isoflurane and spinal anesthesia with lidocaine on oxidative and antioxidant parameters in older patients with inguinal hernia surgery. Methods & Materials: This is a double-blinded randomized clinical trial with parallel design conducted on 70 older patients referred to the surgery department of hospitals in Tehran, Iran during 2018-2019. They were randomly divided into two groups of 35; the first group received general anesthesia with isoflurane and the second group received spinal anesthesia with lidocaine. Blood sampling was performed in two stages; one day before and one day after surgery. Advanced Glycation End Products (AGEs), Advanced Oxidation Protein Products (AOPP), Malondialdehyde (MDA), oxidized Low-Density Lipoprotein (LDL), Ferric-Reducing Ability of Plasma (FRAP), glutathione peroxidase, superoxide dismutase and catalase levels were measured before and after anesthesia using standard methods. Collected data were analyzed in SPSS v.22 software. Results: The Mean±SD age of patients in the lidocaine group was 69.94±8.31 years and in the isoflurane as 70.23±4.98 (P>0.81). In the isoflurane group, there was a significant difference between pre- and postoperative levels of AOPP, MDA, oxidized LDL, FRAP, catalase, glutathione peroxidase and superoxide dismutase. In the lidocaine group, this difference was significant  in MDA, oxidized LDL, catalase and superoxide dismutase.  Conclusion: Given the positive effects of isoflurane on oxidative and antioxidant parameters in older patients with inguinal hernia surgery, it is recommended that this anesthetic be considered in the selection of anesthesia methods and drugs for this group of older patients.